RETHINKING MULTIGROUP: AN INTRODUCTORY ALTERNATIVE APPROACH IN SINGH’S PERSPECTIVE - Peter, Chinedu; Abdullahi, Balarabe (FUDMA JOURNAL OF SCIENCES, 2025)
The analysis of multigroups—multisets defined over group structures—necessitates robust mathematical frameworks. Singh's dressed epsilon notation offers an elegant approach to this analysis by extending traditional set membership concepts to accommodate multiplicity within sets. This notation introduces a refined membership symbol that conveys additional information about the multiplicity of elements within a multiset. By employing Singh's dressed epsilon method, one can more effectively verify properties of multigroups. This approach not only streamlines the representation of multigroup characteristics but also facilitates deeper insights into their structural properties, thereby advancing the theory.